Factor Frequency For The Pre-Elderly And Elderly At Posyandu Elderly X Yogyakarta - Rimenda Lydia; Yeny Sulistyowati; Silvia Dewi Setyaningrum (Journal of Ageing And Family, 2022)
Background: Factors which are directly related to the food frequency is age, where at the age of 50 years the human body starts with health problems due to decreased organ function that affect to the food frequency and environment. In this condition of degenerative disease began to emerge, such as: arthritis, osteoporosis, diabetes mellitus, heart disease, hypertension, cancer, kidney, Alzheimer’s, digestive disorders and endocrine disorders/metabolic. Objective: To find out factors related to the food frequency for the pre-elderly and elderly at Posyandu Elderly Hatsera Kampung Gendeng RW 17 Sub Baciro, Gondokusuman District Yogyakarta. Methods: This study was based on observational research with cross sectional design, aimed to explore the factors that affect the variables that exist (education, income, self-sufficiency and types of degenerative diseases). The research sample was pre-seniors and seniors who met the study criteria. Data were analyzed by chi-square test. Total samplings were 61 people. Results: The samples were consisting of pre-elderly and elderly aged 45-57 years were 29 people (47.5%) and aged 58-69 years were 32 people (52.5%). Analysis of data with the level of significant 95% (α= 0,05) obtained are: 1. There was correlation between education with food frequency (p=0.045), the significance of these variables were moderate (c=0.322). 2. The correlation between income with food frequency (p=0.047), the significance of these variables were moderate (c=0.397). 3. There was correlation between self-sufficiency with food-frequency (p=0.003), the significance of these variables were moderate (c=0.458). 4. There was correlation between types of degenerative diseases with food-frequency (p=0.016), the significance of these variables were moderate (c=0.365). Conclusion: There were significant correlation between levels of education, income, self-sufficiency, and types of degenerative diseases with food frequency.Key words: Food frequency pre-elderly and elderly, education, income, self-sufficiency, types of degenerative diseases.